MIT Press direct. (MIT Press, 2019)
Provides access to ebooks and journals published by the MIT Press. Launch of MIT Press Direct in January 2019 as an independent, cost-effective, and accessible way for libraries to offer MIT Press ebooks to their patrons. In 2020, we expanded the utility and reach of the platform by incorporating our journals, and in 2022 we added the essential research tool CogNet to the collection.